2008
DOI: 10.1007/s12223-008-0045-7
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of PAHs by ligninolytic enzymes of Irpex lacteus

Abstract: The ligninolytic fungus Irpex lacteus was shown as an efficient degrader of oligocyclic aromatic hydrocarbons (PAHs; 'polycyclic aromatic hydrocarbons') possessing 3-6 aromatic rings in complex liquid media. The strain produced mainly Mn-dependent peroxidase in media without pollutants. Activity of ligninolytic enzymes was higher in a N-limited medium. However, after contamination with PAHs (especially pyrene) the values increased and significant activity of Mn-independent peroxidase appeared in the complex me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 36 publications
(22 reference statements)
2
36
0
1
Order By: Relevance
“…I. lacteus reduced peroxidase production until the third week of incubation, when MnP production increased again, together with a peak of DyP, which was able to oxidize high-redox-potential substrates such as anthraquinones. DyP appeared when the carbon/nitrogen ratio in the cultures was very low, which is in accordance with the production profile reported by Cajthaml et al (8) in I. lacteus liquid cultures spiked with polycyclic aromatic hydrocarbons (PAHs). Laccase was not detected, which suggests that both DyP and MnP are the main oxidative enzymes secreted by I. lacteus under these culture conditions.…”
Section: Discussionsupporting
confidence: 90%
“…I. lacteus reduced peroxidase production until the third week of incubation, when MnP production increased again, together with a peak of DyP, which was able to oxidize high-redox-potential substrates such as anthraquinones. DyP appeared when the carbon/nitrogen ratio in the cultures was very low, which is in accordance with the production profile reported by Cajthaml et al (8) in I. lacteus liquid cultures spiked with polycyclic aromatic hydrocarbons (PAHs). Laccase was not detected, which suggests that both DyP and MnP are the main oxidative enzymes secreted by I. lacteus under these culture conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Such compounds were also showed to be products of PAH degradation [35]. The study of influence of some products from PAH degradation [44][45][46] on laccase production revealed that the presence of phthalic acid or 2,2'-diphenic acid did not result in a noticeable increase in laccase production by P. ostreatus D1 and that catechol inhibited it completely.…”
Section: Discussionmentioning
confidence: 99%
“…However the presence of chrysene, benzo[a]anthracene, benzo[a]pyrene or benzo[g,h,i]perylene did not affect the ligninolytic enzyme activity. Authors attributed this to a lower solubility that significantly influences the availability of the compounds for the organisms [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations